Estudio de Adaptación de siete Pastos y tres mezclas forrajeras con la utilización de Lactofermento en la Comunidad San Francisco, Parroquia Toacaso, Provincia de Cotopaxi, período 2018-2019. - Tapia Chiluisa, Estalin Andrés (2019)
This research was conducted in the community San Francisco, located in the parish of Toacaso, province of Cotopaxi, which assessed the adaptation of seven grass and three mixes forage with the use of lactofermento. An experimental design was used in split-plot (A x) obtaining twenty treatments with three replications; statistical analysis helped determine the best treatment on the basis of variables to evaluate which are: germination, plant height, coverage, production and nutritional content of pastures. Where the white clover with 20.59% protein, 2.04% fat, Ryegrass present 94.67% coverage and 26.25% of crude fiber, what it means to ensure the feeding of livestock. Also the mixture of radicchio with blue grass and Red clover showed high percentages in the variables needed for feeding cattle, with 83.25% humidity, 17.94% protein, 25.34% of crude fiber, 12.14% ash. The cost of white clover in four square meters is $0.03 cents, and per hectare $75.00, ryegrass in four square meters has a price of $0.06 cents, and per hectare $150.00.The mixture has a price of $0.15 cents in four square meters and per hectare $375.00.